Implementation and preliminary effectiveness of a real‐time pain management smartphone app for adolescents with cancer: A multicenter pilot clinical study. Issue 10 (19th April 2017) - Jibb, Lindsay A.; Stevens, Bonnie J.; Nathan, Paul C.; Seto, Emily; Cafazzo, Joseph A.; Johnston, Donna L.; Hum, Vanessa; Stinson, Jennifer N.
Abstract: Background: Pain in adolescents with cancer (12–18 years) is common and negatively impacts health‐related quality of life (HRQL). The Pain Squad+ smartphone app, which provides adolescents with real‐time pain self‐management support, was developed to address this issue. This study evaluated the implementation of the app to inform a future randomized controlled trial (RCT) and obtain treatment effect estimates for pain intensity, pain interference, HRQL, and self‐efficacy. Procedure: A one‐group baseline/poststudy design with 40 adolescents recruited from two pediatric tertiary care centers was used. Baseline questionnaires were completed and adolescents used the app at least twice daily for 28 days, receiving algorithm‐informed self‐management advice depending on their reported pain. A nurse received alerts in response to sustained pain and contacted adolescents to assist in pain care. Poststudy questionnaires were completed. Descriptive analyses, with exploratory inferential testing conducted on health outcome data, were used to address study aims. Results: Most (40/52; 77%) eligible adolescents participated. Two participants withdrew participation. Intervention fidelity was impacted by technical difficulties (occurring for 15% of participants) and a prolonged time for nurse contact in the event of sustained pain. Adherence to pain reporting was 68.8 ± 38.1%. Outcome measure completion rates were high and the intervention was acceptable to participants. Trends in improvements in pain intensity, pain interference, and HRQL were significant, with effect sizes of 0.23–0.67. Conclusions: Implementation of Pain Squad+ is feasible and the app appears to improve pain‐related outcomes for adolescents with cancer. A multicenter RCT will be undertaken to examine app effectiveness.